A hybrid filtration–phytoremediation approach for pollutant reduction in laundry wastewater using Spider Plant (Chlorophytum comosum) - Amnan Haris; Trida Ridho Fariz; Abdul Jabbar; Rifa’ Atunnisa; Andin Vita Amalia; Andhina Putri Heriyanti; Andin Irsadi; Sri Ngabekti; Rizda Amalia Putri; Putri Alifa Kholil (Sustinere: Journal of Environment and Sustainability, 2026)
The rapid growth of the laundry industry in Indonesia has led to a significant increase in the use of synthetic detergents, consequently resulting in the discharge of untreated wastewater into aquatic environments. Detergents, while effective in cleaning, pose ecological risks by inhibiting oxygen transfer and disrupting respiratory systems in aquatic ecosystems. This study aims to evaluate the effectiveness of sequential wastewater treatment processes involving filtration and/or phytoremediation using Chlorophytum comosum (spider plant) in reducing key pollutants, namely surfactants, phosphate, and chemical oxygen demand (COD). Environmental parameters such as pH, temperature, and dissolved oxygen (DO) were also monitored. Five treatment setups were designed with triplicate reactors for each: (I) control (untreated), (II) filtration only, (III) phytoremediation only, (IV) filtration followed by phytoremediation, and (V) phytoremediation followed by filtration. Pollutant concentrations were measured before treatment and after 14 days of intervention. The results indicated that the treatment sequence significantly influenced pollutant reduction. The most effective configuration (Treatment V) involved phytoremediation followed by filtration, achieving reductions in phosphate (0.04 mg/L; 62.58% removal), surfactants (0.34 mg/L; 98.12% removal), and COD (16.66 mg/L; 95.10% removal). The treatment also enhanced water quality parameters, with final measurements of pH 7.9, temperature 26.3 °C, and DO 5.7 mg/L. The novelty of this study lies in the evaluation of the treatment sequence combining phytoremediation and filtration, revealing that initiating the process with Chlorophytum comosum–based phytoremediation followed by filtration achieved the highest pollutant removal efficiency. This configuration introduces a low-cost, nature-based, and scalable solution for sustainable laundry wastewater management. This integrated phytoremediation–filtration system can significantly reduce nutrient and surfactant loads, thereby preventing eutrophication and enhancing the ecological quality of urban aquatic environments.